Plant–Human Commoning: Navigating Enclosure, Neoliberal Conservation, and Plant Mobility in Exurban Landscapes. Issue 6 (2nd November 2018) - Cooke, Benjamin; Lane, Ruth
Abstract : Conservation on private land in exurban landscapes is habitually framed around the private property parcel. Neoliberal conservation programs that position private property as exclusive territory for conservation action are compounding the property-centric focus of exurban conservation practices. This framing conflicts with an understanding of ecologies as socionatures that are geographically dispersed and temporally contingent, as well as the implications of landscape-scale species migration driven by climate change. Here we explore whether the agency and mobility of plants across property boundaries offer an avenue for more meaningful alternatives to exurban conservation that are not bounded by the territory of private property. The conservation practices of exurban landholders in Victoria, Australia, were explored through qualitative interviews and property walks. The mobility of plants in the form of spreading, seeding, and suckering through fence lines reflects a form of more-than-human territorial enactment that can bring attention to shared and relational ecologies, while unsettling the notion of control over conservation practice that accompanies property ownership. We explore the potential of the recent reengagement with commoning—in the form of plant–human commoning practices—to position plants as active collaborators in commoning, rather than as the objects of human commoning. Although attentive to the challenges of multispecies coalitions in conservation, we suggest that plant–human commoning could offer new possibilities for conservation that is grounded in the affordances of plants, as a counter to neoliberal governance and the individualization and privatization of exurban landscapes.